Choice of parents of cowpea bean by means of multivariate analysis - Dos Santos, Adriano; Ceccon, Gessí; Machado, Sivanilza Teixeira; Rodrigues, Erina Vitório; Gonçalves, Manoel Carlos (Agrarian, 2015)
The aim of this study was to quantify genetic divergence among cowpea bean genotypes by means of Integrated Multivariate Analysis, with the purpose of assisting selection of parents for development of new cultivars. A randomized block experimental design was used with 32 treatments and 4 replications. There is agreement among the multivariate techniques applied in clustering of the genotypes. The genotypes show genetic variability, exhibiting potential for use in breeding programs. The crosses carried out between the genotypes MNC02-675F-9-3 and MNC03-737F-5-10 with the genotypes MNC03-737F-5-11, MNC03-737F-5-1, MNC03-725F-3 and MNC03-737F-5-9 may lead to obtaining segregating progenies with high yield potential and an increase in the probability of select superior genotypes in the segregating generations.